Study of the effect of ultrasonic-assisted extraction based on the Box-Behnken design on the phenolic compound content of Hammada scoparia leaves and evaluation of their antioxidant and antibacterial activities - Meriam Salemi; Hassiba Metrouh-Amir; Nadir Amir; Hamza Moussa (Croatian Journal of Food Science and Technology)
Hammada scoparia is a plant of the Chenopodiaceae family. It represents a potential source of polyphenols and is used in traditional medicine in many countries. This research was carried out to evaluate the influence of ultrasound-assisted extraction parameters (ethanol concentration (30-70%), temperature (20-60 °C), time (10-30 min), and solvent-to-solid ratio (30-60 v/w) on total phenolic compound and total flavonoid contents, as well as the antioxidant capacity (DPPH assay) of H. scoparia, using the response surface methodology (RSM) approach and a Box-Behnken design (BBD). The obtained optimal extract of H. scoparia was used to evaluate ferric and molybdate reducing powers and ABTS scavenging activity as well as the antibacterial activity. Based on the BBD results, the extraction conditions, which gave the highest contents of phenolic compounds and flavonoids and the greatest DPPH activity, are: an extraction time of 30 minutes, a temperature of 20 °C, an ethanol concentration of 46.95%, and a liquid-to-solid ratio of 60 mL/g. The results of the determination of antioxidant activity revealed that H. scoparia extract inhibited free radicals DPPH˙ and ABTS˙, and reduced ferric and molybdate through different mechanisms. Concerning the antibacterial activity, the results obtained showed that H. scoparia extract was found to be active against all tested bacterial strains, with the exception of Escherichia coli ATCC 25922. H. scoparia optimal extract could be a promising source for the pharmaceutical industry and food applications.